Modernisasi Manajemen Kurikulum Pendidikan di Pondok Pesantren Attarbiyatussakilah Kendari - Muhammad Najib; Hasibuddin; Syahid, Akhmad (Program Pascasarjana Universitas Muslim Indonesia, 2023)
Pondok Pesantren Attarbiyatussakilah Kendari as an Islamic boarding school is a representation of the modernization of education in Indonesia. In its management, the Attarbiyatussakilah Islamic Boarding School has implemented management integration in the form of an integration between a vocational-based formal education curriculum and a religiously charged Islamic boarding school curriculum, as well as the application of scientific educational operational management including planning, organizing, actualizing, implementing, as well as control and evaluation (POAC) in the integration of the curriculum. The goal of this study is to explain how SMK Life Skill Pondok Pesantren Attarbiyatussakilah Kendari is modernizing the way they manage their education curriculum. This study uses a qualitative method with a descriptive approach through field studies at the Attarbiyatussakilah Islamic Boarding School. Triangulation of techniques and triangulation of sources will be used to confirm the results of each study. The results of this study indicate that modernization in the form of management integration, especially in the vocational curriculum in the Islamic boarding school curriculum, carried out by the Attarbiyatussakilah Islamic Boarding School, is carried out with the principles of management operationalization, planning, organizing, implementing, and evaluating.